Type I Gaucher disease with bullous pemphigoid and Parkinson disease: A case report. Issue 13 (March 2018) - Le Peillet, Damien; Prendki, Virginie; Trombert, Véronique; Laffitte, Emmanuel; Assal, Frédéric; Reny, Jean Luc; Serratrice, Christine
Abstract: Rationale: Gaucher disease (GD) is a rare genetic lysosomal storage disorder inherited in an autosomal recessive pattern. GD is due to the deficiency of a lysosomal enzyme, acid beta-glucosidase (or glucocerebrosidase). Type 1 Gaucher disease (GD1) is characterized by thrombocytopenia, anemia, an enlarged spleen, and liver as well as bone complications (Erlenmeyer flask deformity, osteoporosis, lytic lesions, pathological and vertebral fractures, bone infarcts, and avascular necrosis leading to degenerative arthropathy). The diagnosis is usually made in first decades but is sometimes delayed. Parkinson disease, neoplasia, and immune system abnormalities may be associated with GD1. Patient concerns: A patient known for hepatosplenomegaly with hyperferritinemia, anemia, and thrombocytopenia was admitted for Lewy body dementia and bullous pemphigoid. Diagnoses: Type 1 Gaucher disease. Intervention: No specific treatment started. Outcomes: patient died ten months later due to pneumonia. Lessons: To the best of our knowledge, this is the first case of the association between GD1, bullous pemphigoid, and Lewy body dementia. We discuss the central role of alpha-synuclein in these pathologies.